2022
DOI: 10.3389/fnut.2022.717064
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Impact of Zinc Deficiency in Human Development

Abstract: Zinc (Zn) deficiency in humans is an emerging global health issue affecting approximately two billion people across the globe. The situation prevails due to the intake of Zn deficient grains and vegetables worldwide. Clinical identification of Zn deficiency in humans remains problematic because the symptoms do not appear until impair the vital organs, such as the gastrointestinal track, central nervous system, immune system, skeletal, and nervous system. Lower Zn body levels are also responsible for multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 88 publications
0
34
0
Order By: Relevance
“…To surpass nutrient deficiency in the human diet, the application of agronomic workflows to increase the amount of a nutrient in the edible part of food crops, by application of fertilizers through soil or foliar spraying, is receiving increasing attention [ 15 , 16 , 17 , 18 , 19 , 20 ]. Among these approaches, Zn fertilization is a short-term and effective strategy [ 15 ], yet its absorption greatly depends on soil pH, organic matter concentration, antagonistic cations (especially in calcareous soils), type of Zn complex and amount of foliar spraying.…”
Section: Introductionmentioning
confidence: 99%
“…To surpass nutrient deficiency in the human diet, the application of agronomic workflows to increase the amount of a nutrient in the edible part of food crops, by application of fertilizers through soil or foliar spraying, is receiving increasing attention [ 15 , 16 , 17 , 18 , 19 , 20 ]. Among these approaches, Zn fertilization is a short-term and effective strategy [ 15 ], yet its absorption greatly depends on soil pH, organic matter concentration, antagonistic cations (especially in calcareous soils), type of Zn complex and amount of foliar spraying.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the underlying mechanism for increased non‐fasting blood glucose, the Panel considered that the decreased zinc blood concentration may be responsible for the observed increase in blood glucose. Zinc is involved in the synthesis, processing and secretion of insulin in pancreatic β‐cells (Cole et al., 2010 ; Poudel et al., 2017 ; Hussain et al., 2022 ). Zinc takes part in the inhibition of glucagon secretion in response to high glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have demonstrated a relationship between dietary zinc content and cancer risk. The anticancer effects of zinc are mostly related to its antioxidant properties ( 3 ). Being a trace element, zinc is essential in various metabolic processes, including protein synthesis, immune response, and gene expression ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%